The Ukrainian Pryazovye: composition, uniqueness, variability of the recreational development - Олександр Бейдик; Олександр Комлєв; Лариса Донченко; Ірина Арсененко; Олеся Топалова; Ірина Донець (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії)
The regulations have been grounded in the article according to which the Ukrainian Pryazovye is positioned as the unique resource-recreational space, cultural-world outlook, landscape-physical-geographical, recreational-tourist resources (available and latent, current and potential) of which are used extremely insufficiently. Bodies, forces and phenomena of nature and society are meant by cultural and ideological resources that affect behavior, character, spiritual and physical development of man during the recreational cycle. Against the background of temporary limitation of the use by the Ukraine of the part of its Azov-Black Sea coast, the Ukrainian Pryazovye receives the option to increase its resource and recreational rating and to strengthen the national recreational and tourist branch as a whole, which requires the balanced, constructive and delicate attitude to this territory.